IMPROVING PUPILS’ VOCABULARY MASTERY BY USING VIDEO SONGS - Ella, Nanda; Sofian, Sofian; Rosnija, Eni (FKIP - Universitas Tanjungpura, 2021)
The research was aimed to improve pupils’ vocabulary by using video songs. This research was a classroom action research which done in two cycles. The subject of this research was the class A6 pupils of TK Immanuel. The researcher observed pupils’ improvement by collecting data through field notes, observation checklist and vocabulary test. The pupils’ behaviour towards the learning process was gathered by field note and observation checklist. The data of vocabulary was obtained by vocabulary test which was assessed through scoring rubric. The result showed those pupils’ problems in recognizing and mentioning the vocabulary had been solved by using video songs as the media of teaching. Furthermore, pupils’ interest in learning vocabulary also improved. It was shown by the pupils’ enthusiasm to pay attention in watching the video and singing together during teaching and learning process. As the conclusion, the media was able to be used in improving pupils’ vocabulary.